PEMANFAATAN MODEL WRF-CHEM DALAM ANALISIS SEBARAN ABU VULKANIK GUNUNG MERAPI (ERUPSI TANGGAL 23 MARET 2020) - Yudistira, Ricko; Indah Sary; Agung Hari Saputra (Jurnal Meteorologi Klimatologi dan Geofisika, 2019)
Volcanic ash is the result of fusion on mountain released into the atmosphere. Volcanic ash has dangerous impact for several sectors as health, agriculture, until flight safety. Therefore, it is important to forecast the direction of volcanic ash distribution to reduce disadvantage caused by volcanic ash. One of the way to forecast volcanic ash is to use the WRF-Chem model. The WRF-Chem model is a numerical weather forecast model with chemistry parameter elements so that it can predict the direction of volcanic ash distribution. On March 27, 2020, Mount Merapi had an eruption which caused volcanic ash to reach a height of about 5000 meters from the crater of the mountain. The results of the WRF-Chem model show the distribution direction of each size and concentration of volcanic ash from the 700mb to 300mb levels. The model results show that the volcanic ash distribution of each levels moves to the Southwest in accordance with the advisory data released by VAAC Darwin. However, the results of the model have a time delay in the distribution of volcanic ash